Assessing the Impact of Inflation and CPI on the Agricultural Economy: A Case Study of Lampung Province's Farmer Exchange Rate - Yusdhika, Aldo WIse Hanjaya; Julianti, Mega; Karsinah, Karsinah (Journal of Economic, Religious, and Entrepreneurship (JoERE), 2025)
This study investigates the effect of inflation and the Consumer Price Index (CPI) on the performance of the agricultural sector in Lampung Province, Indonesia. Given the agricultural sector’s critical role in regional economic development and rural livelihoods, understanding macroeconomic influences is essential. Using secondary time-series data from relevant agencies, the research employs multiple linear regression analysis to assess the relationship between inflation, CPI, and agricultural output performance. The findings indicate that both inflation and CPI significantly affect agricultural productivity. Higher inflation rates are associated with increased production costs and reduced farm income, whereas CPI fluctuations complicate financial planning and price stability for farmers. These results highlight the need for targeted economic policies to stabilize macroeconomic variables and mitigate their adverse effects on the agricultural sector, ensuring long-term sustainability and productivity in rural economies.